Economic Freedom, Globalization, and the Shadow Economy in the European Union Transition Economies: a Panel Cointegration Analysis - Bayar, Yılmaz; Öztürk Ömer Faruk (Organizations and Markets in Emerging Economies, 2019)
The presence of the shadow economy differs considerably among the countries. Therefore, determination of factors behind the differences in the size of cross-country shadow economy becomes more of an issue for designing and implementing the right policies to combat the shadow economy. This study investigates the influence of economic freedom and globalization on the size of the shadow economy in the European Union transition economies employing panel data analysis for the period of 2000–2015. The empirical analysis indicates that economic freedom reduces the size of the shadow economy in the long term in the overall panel, but globalization also has a relatively smaller detractive effsect on the shadow economy in some countries.